Collaborative governance model in the implementation of performance-based village fund allocation in Kalibandung Village, Kubu Raya Regency - Firdaus Firdaus; Herilasti Pujiningsih; Ksatriawan Zaenuddin; Helen Puspita Sari; Anggun Pria Wibowo (Privietlab, 2025)
The Ecology-based District Budget Transfer Policy (TAKE) is an ecological fiscal innovation developed to link financial transfers between government levels and environmental performance at the village level. This study aims to analyze the implementation of TAKE policies in Kalibandung Village, Kubu Raya Regency, and examine the dynamics of collaboration between actors to support performance-based environmental governance. Using a descriptive qualitative approach, this study explores the views and practices of various actors, including regional apparatus organizations (OPDs), village forest management institutions (LPHD), non-governmental organizations (NGOs), and local communities. The analysis is carried out through thematic interpretations that place the Collaborative Governance Framework and Institutional Analysis and Development as the main theoretical lenses. The results of the study show that the implementation of TAKE is influenced by four collaborative dimensions: unequal initial conditions in terms of capacity and access to information; institutional design that is still top-down without deliberative space; strong facilitative leadership at the village level but not yet sustainable at the district level; and collaborative processes that take place partially and have not been institutionalized. These findings confirm that the success of ecological fiscal policies at the local level is not solely determined by the calculation of incentives and technical indicators but by the quality of social interactions, trust, and institutional design that enable collaboration and shared learning. This study contributes to strengthening the theory of Collaborative Governance in the context of village ecological fiscal policy and provides a direction for policy reform towards participatory and sustainable environmental governance.